Функцiональна характеристика мiкроiнкапсульованої тканини аденоми паращитовидної залози людини в умовах in vitro - Пастер, І.П. (Видавничий дім "Академперіодика" НАН України, 2007)
The microencapsulated tissue of human parathyroid adenoma keeps a high functional activity in vitro (in particular, the ability for active parathormone secretion and an adequate reaction to extracellular calcium) that makes it suitable for using it as a transplant in the compensation of the hypofunctional state of the parathyroid system.